Peran Pembiayaan Murabahah Baitul Maal Wat Tamwil dalam Mendukung Perkembangan Usaha Mikro - Euis Naely Minatika; Purwanto Purwanto; Achmad Labib (CV. Ulil Albab Corp, 2024)
This research delves into the pivotal role played by Baitul Maal Wa Tamwil (BMT) in elevating micro-business income, specifically focusing on the impact of Murabahah financing offered by BMT Eka Mandiri in Indonesia. Employing a qualitative method, the study aims to comprehensively explore and understand the multifaceted role of Murabahah financing in supporting micro-businesses. The overarching goal is to shed light on how this form of financing contributes to the economic well-being of micro-entrepreneurs. The research findings underscore the positive and transformative impact of Murabahah financing provided by BMT Eka Mandiri on the income of micro-business actors. One of the key benefits identified is facilitating easier and more affordable access to capital. This improved accessibility empowers micro-business owners to enhance their production capacity and diversify their range of products, subsequently opening avenues for increased revenue. The Murabahah financing mechanism employed by BMT Eka Mandiri addresses the financial needs of micro-businesses and catalyzes business growth. By providing a structured and Sharia-compliant approach to financing, BMT Eka Mandiri fosters an environment where micro-entrepreneurs can thrive and expand their ventures. Furthermore, the research reveals that this form of financing contributes to the resilience and sustainability of micro-businesses.